In vitro evaluation of anticancer and biological activities of synthesized manganese oxide nanoparticles. Issue 8 (28th June 2016) - Khan, Shahanavaj; Ansari, Anees A.; Khan, Abdul Arif; Abdulla, Maha; Obeed, Omar Al-; Ahmad, Rehan
Abstract : This paper presents the results from a systematic study into the characterization and anticancer and biological activity of synthesized super-paramagnetic manganese oxide nanoparticles (Mn3 O4 -NPs). Abstract : This paper presents the results from a systematic study into the characterization and anticancer and biological activity of synthesized super-paramagnetic manganese oxide nanoparticles (Mn3 O4 -NPs). The Mn3 O4 -NPs showed an IC50 value of 666.44 μg mL −1 on the HT29 human colorectal cell line. Furthermore, we investigated the molecular mechanism of Mn3 O4 -NPs for the inhibition of Bcl-2 and Bcl-xL through an in vitro study. Bcl-2 and Bcl-xL are key signaling regulators of the programmed cell death pathway and ensure proper apoptosis and have been proposed as a novel target for anticancer therapy. The down-regulation of Bcl-2 and Bcl-xL on the HT29 cancer cell line showed that the NPs under study could be useful in the treatment of cancer. The down-regulation of the anti-apoptotic regulators Bcl-2 and Bcl-xL enhances cytotoxicity in colon carcinoma cells connected with the induction of apoptosis. Moreover, the in vitro haemolysis study antibacterial tests showed that Mn3 O4 -NPs have no significant toxicity and antibacterial activity, thereby exhibiting their biocompatibility and reliability in biomedical sciences.